Human pharmaceuticals in marine mussels: Evidence of sneaky environmental hazard along Italian coasts. (December 2020) - Mezzelani, Marica; Fattorini, Daniele; Gorbi, Stefania; Nigro, Marco; Regoli, Francesco
Abstract: Despite the increasing interest for pharmaceuticals in the marine environment, their accumulation in wild organisms and consequent environmental hazards are still poorly known. The Mediterranean Sea is highly challenged by the density of coastal populations, large consumption of pharmaceuticals and their often limited removal by Wastewater Treatment Plants (WWTPs). In this respect, the present study aims to provide the first large-scale survey on the distribution of such contaminants of emerging concern in native mussels, Mytilus galloprovincialis from Italian coasts. Organisms were collected from 14 sites representative of relatively unpolluted marine waters along the Adriatic and Tyrrhenian Sea and analysed for 9 common pharmaceuticals including Non-Steroidal Anti-Inflammatory Drugs (NSAIDs: Diclofenac DIC, Ibuprofen IBU, Ketoprofen KET and Nimesulide NIM), the analgesic Acetaminophen AMP, the antiepileptic Carbamazepine CBZ, the antihypertensive Valsartan VAL, the anxiolytic Lormetazepam LOR and the antidepressant Paroxetine PAR. Results indicated the widespread occurrence of the majority of pharmaceuticals in mussel tissues: CBZ was measured in >90% of analysed samples, followed by VAL (>50%), PAR (>40%), and DIC (>30%), while only AMP and KET were never detected. Heterogeneous tissue concentrations ranged from a few units up to hundreds of ng/g (d.w.), while seasonal and interannual variability, investigated over 4 years, did not highlight any clear temporal trend. Limited differences obtained between the Adriatic and Tyrrhenian Sea, as well as coastal versus off-shore sampling sites, suggest that analysed levels of pharmaceuticals in mussels tissues should be considered as baseline concentrations for organisms collected in unpolluted areas of the Mediterranean. This study provided the first unambiguous evidence of the widespread occurrence of pharmaceuticals in marine mussels from Italian coasts, giving novel insights on the potential ecotoxicological hazard from such compounds in marine species. Graphical abstract: Image 1 Highlights: Pharmaceuticals are ubiquitously present in tissues of Mediterranean mussels. Organisms contained drugs of several therapeutic classes. Carbamazepine was measured in more than 90% of analysed samples. 91% of analysed mussels contained at least 1 drug, 55% at least 3. Seasonality had a limited influence on pharmaceuticals bioaccumulation.